2006
DOI: 10.1007/s00268-005-0485-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Circulating Tumor Cells in the Peripheral Blood of Patients with Colorectal Cancer Using RT‐PCR: Significance of the Prediction of Postoperative Metastasis

Abstract: Using RT-PCR for the detection of CEA mRNA is feasible and may be a promising tool for early detection of micrometastatic circulating tumor cells in CRC patients. CRC patients expressing positive CEA mRNA in peripheral blood have a significantly higher risk of postoperative metastasis. Nevertheless, confirmation of CEA mRNA as a prognostic predictive factor requires the continuation of patient follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
70
1
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 35 publications
(56 reference statements)
7
70
1
5
Order By: Relevance
“…There are tumor markers detectable in gastric patients that can predict early stages of metastasis; some of these markers are detectable in lymph nodes, while others are present in peripheral blood (Zieglschmid et al, 2005;Ohlsson et al, 2006). The detection rate of circulating tumor cells in peripheral blood from gastric cancer patients is in the range from 27 to 88% (Conzelmann et al, 2005;Wang et al, 2006;Lloyd et al, 2006). Although many markers have been investigated individually or in several panels, the lack of both sensitivity and specificity was shown in these experiments.…”
Section: Discussionmentioning
confidence: 78%
“…There are tumor markers detectable in gastric patients that can predict early stages of metastasis; some of these markers are detectable in lymph nodes, while others are present in peripheral blood (Zieglschmid et al, 2005;Ohlsson et al, 2006). The detection rate of circulating tumor cells in peripheral blood from gastric cancer patients is in the range from 27 to 88% (Conzelmann et al, 2005;Wang et al, 2006;Lloyd et al, 2006). Although many markers have been investigated individually or in several panels, the lack of both sensitivity and specificity was shown in these experiments.…”
Section: Discussionmentioning
confidence: 78%
“…Forty-six references were assessed in full, and a further 32 studies were excluded (Figure 1). Eight studies were excluded as they reported only on preoperative blood sampling (Bessa et al, 2001;Fujita et al, 2001;Wong et al, 2001;Zhang et al, 2005;Douard et al, 2006;Iinuma et al, 2006;Wang et al, 2006;Friederichs et al, 2007). Nine studies were excluded as they contained data from which outcomes could not be extracted, of which four were excluded as they combined positive results of molecular detection of multiple samples and their effect on prognosis (Hardingham et al, 2000;Guller et al, 2002;Bosch et al, 2003;Koyanagi et al, 2008), and five were excluded as it was impossible to extract the data for outcomes of interest (White and Griffiths, 1976;Funaki et al, 1998;Wyld et al, 1998;Conzelmann et al, 2005;Wang et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…In patients with colorectal cancer, the presence of CTC in peripheral blood was repeatedly confirmed and their detection ranged from 20% for localized disease and 60% in advanced CRC [10][11][12][13][14][15][16][17][18]. The clinical relevance of CTC as an independent prognostic factor was documented for cases in patients with positive CTC at diagnosis who had poorer prognosis than patients with negative CTC [10,[12][13][14][16][17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…Interestingly, some authors have performed RT-PCR even without prior pre-concentration [10,27]. Aside from just detecting their presence, the molecular profile of CTC may serve as a predictor of treatment response and survival as demonstrated in several studies [11,12,[28][29][30]. The technique known as the "liquid biopsy" has recently generated a strong interest among molecular oncologists as a viable alternative in cases where tissue sampling is not available [31].…”
mentioning
confidence: 99%